PEMANFAATAN EKSTRAK DAUN RAMBUTAN (Nephelium lappaceum L.) PADA TRANSPORTASI LOBSTER AIR TAWAR (Procambarus clarkii) DENGAN SISTEM KERING - Syamsunarno, Mas Bayu; Syukur, Abdul; Munandar, Aris (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2019)
Immotilization of live red swamp crayfish (Procambarus clarkii) in this research a used Nephelium lappaceum leaf extract as a natural anesthetic. The aims of this research were to determine the best concentration of the Nephelium lappaceum leaf extract as red swamp crayfish anesthesia and the optimum time of dry transportation system. This research method was an experimental laboratory with two replication with each concentration 0 ppm, 171 ppm, 294 ppm, 503 ppm, 863 ppm, 1479 ppm, 2535 ppm, 4345 ppm, and 7447 ppm. The study showed that the content of secondary metabolites from extracts of Nephelium lappaceum leaf were alkaloids, saponins, phenols hydroquinones, tannins, and flavonoids. The optimum concentration for anesthesia red swamp crayfish is 7447 ppm with passed out on 112 minutes and time conscious at 3 minutes. Dry transport time that produces the best survival rate was approximately 8 hours with the survival rate of 100%. The results of the measurement of the quality of the water before it extracts included, among others, the temperature of 29.2ºC, pH 5.9, DO 7.1 mg/L and TAN 0 mg/L. While the results of measurements of water quality after extracts included, among others, the temperature was 29ºC, pH 6.5, DO 6.8 mg/L, and TAN 0.026 mg/L.